ART AS A TOOL FOR ACHIEVING SOCIAL INCLUSION: AUTOBIOGRAPHICAL PRACTICES IN MIGRANT CONTEXTS - Nasibeh Mousvi Irani (PEOPLE: International Journal of Social Sciences, 2025)
This paper examines how migrant artists employ autobiographical art to navigate displacement, negotiate their identities, and promote a sense of belonging in new cultural contexts. In migration settings, art extends beyond fairness, functioning as a site of memory, resilience, and activism that links personal experience with broader social narratives. Adapting a constructivist epistemology, the study combines in-depth interviews with practising artists, autoethnographic reflection, and analysis of creative works. This qualitative approach highlights both individual trajectories and shared challenges, positioning the voices of migrant artists at the centre of interpretation. Findings identify five key themes: Artistic Journeys, shaped by migration, education, and career transformation; Autobiographical Art as Identity, Healing, and Resistance, where art becomes a tool for recovery and advocacy; Heritage and Cultural Continuity, which sustains traditions across transnational spaces; Social Challenges and Structural Barriers, including discrimination and institutional inequities; and Cross-Cultural Collaboration and Social Responsibility, reflecting artists’ commitments to dialogue, community-building, and social change. The analysis draws on Bhabha’s Third Space Theory to illuminate hybrid identities, Narrative Identity Theory to emphasise storytelling and resilience, and Critical Race and Intersectionality Theory to examine structural inequities. Levitt’s notion of Social Change through Art further demonstrates how creative practices catalyse dialogue and collective empowerment. By situating migrant artists’ autobiographical works within these theoretical frameworks, the study demonstrates that art serves not only as a means of survival and identity construction but also as a powerful tool for promoting social awareness and inclusion. It argues that creative practices play a critical role in fostering intercultural exchange and generating transformative change within multicultural societies.